How common are seizures in the heidenhain variant of creutzfeldt-jakob disease? A case report and systematic review. (April 2021) - Muthusamy, Subramanian; Garg, Priya; Chandra, Ronil V.; Seneviratne, Udaya
Highlights: The Heidenhain variant of Creutzfeldt-Jakob Disease accounts for up to 20% of all cases of CJD. Imaging and electrographic abnormalities are typically localised to the posterior cerebral cortices. Seizures occur in 15% of all cases of CJD but are uncommon in the HvCJD. Under-recognition of seizures and differential cortical excitability may account for this difference. Abstract: The Heidenhain variant of Creutzfeld-Jakob disease (HvCJD) is a relentlessly progressive and fatal neurodegenerative disorder characterised by prominent visual features early in its clinical course. However, seizures are uncommonly reported in HvCJD. The case history of a patient admitted to our institution with HvCJD and seizures is described followed by a systematic review of the association between HvCJD and seizures. A systematic search of the databases Medline, PubMed, and PsycInfo was conducted, from inception to November 2019, using keywords relating to 'Creutzfeldt-Jakob disease' and 'Heidenhain variant', to ascertain the frequency of seizures in HvCJD, as well as, seizure semiology and electrographic features. The Preferred Items Reporting for Systematic Reviews and Meta-Analyses (PRISMA) guidelines were followed in the construction of this systematic review. All studies, including case reports of patients who met the diagnostic criteria for HvCJD where details pertaining to clinical presentation, imaging, biochemical and EEG findings were available were included. There were 46 articles reporting on a total of 73 patients. Seizures occurred in only four out of 73 cases (5.5%). The semiology of these seizures were focal motor seizures with or without secondary generalisation and occipital lobe seizures. Imaging and electrographic findings were most commonly abnormal in the posterior cerebral cortices (in particular the occipital and occipito-parietal regions). This systematic review suggests that seizures are uncommon in HvCJD despite the frequency of imaging and electrographic abnormalities in the posterior cerebral regions. A key limitation of this systematic review is the variability of publications in terms of incomplete reporting of clinical data, in particular potential under-reporting of seizures, as well as follow up, which may have contributed to the lower frequency of seizures reported in patients with HvCJD.